Stripping in HMA Mixtures: State-of-the-Art and Critical Review of Test Methods - Kiggundu, Badru M.; Roberts, Freddy L. (National Center for Asphalt Technology, 1988)
This report presents review summaries of the state-of-the-art regarding stripping in hot mix asphalt (HMA) mixtures. The review stresses efforts concerned with methods development, evaluation and presents a critical review of select methods including Lottman (NCHRP 246), Tunnicliff-Root (NCHRP 274), Immersion Compression, 10-minute boil test, and the Nevada dynamic strip method. The results of the critical review of methods indicated the following ranking order: Lottman test, Tunnicliff-Root test, 10-Minute Boil test, Immersion Compression, and Nevada Dynamic Strip test. The basis of the analysis was a proposed success/failure pattern which was developed using published data on stripping. Other products of this research include: proposed relationship between stripping theories and mechanisms, and an appended summary of findings from surveys of the users of the stripping tests. (44 p.)